Sorption and subsequent photodegradation of crystal violet dye by CdS and Cu@CdS prepared using Desulfovibrio vulgaris AU16 - Shivesh Kumar Azad; Maulin P. Shah; Manoj Kumar Gangwar; Prashant D. Kunjadia; Madhu Kumari; Fuad Ameen; Kumar Suranjit Prasad (Journal of Water Process Engineering, 2026)

Variation in patterns of production and water-use efficiency among agroecosystems - Olivia L. Hajek; Nicole E. Kaplan; Shefali Azad; Philip A. Fay; Makki Khorchani; Amanda M. Nelson; Adam P. Schreiner-McGraw; Lori J. Abendroth; Claire Baffaut; John Baker; Brandon T. Bestelmeyer; Elizabeth H. Boughton; et al. (Science of The Total Environment, 2025)

Investigating local residence time and thermomechanical stress profile in twin-screw extrusion of plant proteins by using the moving particle semi-implicit simulation method - Felix Ellwanger; Laurids Pernice; Heike P. Karbstein; M. Azad Emin (Journal of Food Engineering, 2023)

Design, synthesis, biological evaluation and in silico studies of EGFR inhibitors based on 4-oxo-chromane scaffold targeting resistance in non-small cell lung cancer (NSCLC) - Kshipra S. Karnik; Aniket P. Sarkate; Shailee V. Tiwari; Rajaram Azad; Pravin S. Wakte (Medicinal Chemistry Research, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Properties of metakaolin-based green pervious concrete cured in cold and normal weather conditions - Armin Azad; Sayed-Farhad Mousavi; Hojat Karami; Saeed Farzin; Omid Rezaifar; Ali Kheyroddin; Vijay P. Singh (European Journal of Environmental and Civil Engineering, 2022)

Influence of the water–sediment interaction on the major ions chemistry and fluoride pollution in groundwater of the Older Alluvial Plains of Delhi, India - Shakir Ali; Shashank Shekhar; Trupti Chandrasekhar; Akhilesh Kumar Yadav; Naresh Kumar Arora; Chandrashekhar Azad Kashyap; Prosun Bhattacharya; S P Rai; Prabhas Pande; Dornadulla Chandrasekharam (Journal of Earth System Science, 2021)

N-Benzylation of 6-aminoflavone by reductive amination and efficient access to some novel anticancer agents via topoisomerase II inhibition - Nitin M. Thorat; Aniket P. Sarkate; Deepak K. Lokwani; Shailee V. Tiwari; Rajaram Azad; Shankar R. Thopate (Molecular Diversity, 2021)

Correction to: Polymyxin B causes DNA damage in HK-2 cells and mice - B. Yun; T. Zhang; M. A. K. Azad; J. Wang; C. J. Nowell; P. Kalitsis; T. Velkov; D. F. Hudson; J. Li (Archives of Toxicology, 2018)

Polymyxin B causes DNA damage in HK-2 cells and mice - B. Yun; T. Zhang; M. A. K. Azad; J. Wang; C. J. Nowell; P. Kalitsis; T. Velkov; D. F. Hudson; J. Li (Archives of Toxicology, 2018)

Utility of ITS1 as a molecular tool for reliable identification of Henosepilachna pusillanima and H. septima (Coleoptera: Coccinellidae) - G. T. BEHERE; D. M. FIRAKE; P. S. BURANGE; P. D. FIRAKE; N. S. AZAD THAKUR; S. V. NGACHAN (Journal of Genetics, 2015)

Emerging evidence for CHFR as a cancer biomarker: from tumor biology to precision medicine - Sarah Derks; Arjen H. G. Cleven; Veerle Melotte; Kim M. Smits; Johann C. Brandes; Nilofer Azad; Wim van Criekinge; Adriaan P. de Bruïne; James G. Herman; Manon van Engeland (Cancer and Metastasis Reviews, 2013)

An outbreak of pine lappet moth, Kunugia latipennis, in mid-altitude hills of Meghalaya state, India - D. M. Firake; G. T. Behere; P. D. Firake; N. S. Azad Thakur; Z. B. Dubal (Phytoparasitica, 2012)

Distribution of arbuscular mycorrhizal fungi in marshy and shoreline vegetation of Deepar Beel Ramsar Site of Assam, India - Bula Choudhury; M. C. Kalita; P. Azad (World Journal of Microbiology and Biotechnology, 2010)

Variability in Symbiotic Effectiveness of Native Rhizobia in Acid Stress - B. Choudhury; P. Azad; M. C. Kalita (Current Microbiology, 2010)

Pseudomonas aeruginosa inducing rice resistance againstRhizoctonia solani: Production of salicylic acid and peroxidases - R. Saikia; R. Kumar; D. K. Arora; D. K. Gogoi; P. Azad (Folia Microbiologica, 2006)